Microplastics in the aquatic environment: implications for post-harvest fish quality - Rao, B. Madhusudana (Indian Journal of Fisheries, 2019)
Though fish meat is good for health, its consumption is determined by post-harvest quality parameters. The â€œuse and disposeâ€ attitude of the public towards plastics coupled with inadequate waste management has led to extensive accumulation of plastic debris in the aquatic environment. Microplastics (plastic particles of <5mm in their longest dimension) in the aquatic environment and fish gut is an emerging concern that has been reported from different regions of the world. The degradation of plastic polymers to micro- and even to nano sized particles smaller than 100 nm size is of recent major concern. Micro- and nanoplastics are basically inert but they tend to sorb toxic pollutants and harmful microorganisms. Moreover, chemicals added to plastic to impart functional properties pose threat to human health. Fish, either by passive ingestion or active foraging accumulate microplastics in their guts. However, there is paucity of documented evidence on the adverse effect of microplastics on human health due to consumption of such fish. Protocol for the determination of quantity of microplastics in fish flesh needs to be standardised and quality standard to be fixed for the quantity of microplastics that would be considered as a food hazard. There exists an imminent need to perform risk analysis in order to categorise microplastic as a food hazard in fish meant for human consumption. Until then there is no justification to reduce the consumption of fish and fishery products due to apprehension of presence of microplastics.